Evaluation of an early detection tool for social-emotional and behavioral problems in toddlers: The Brief Infant Toddler Social and Emotional Assessment - A cluster randomized trial - Carter Alice S; Jansen Wilma; Kruizinga Ingrid; Raat Hein (BMC, 2011)
Abstract Background The prevalence of social-emotional and behavioral problems is estimated to be 8 to 9% among preschool children. Effective early detection tools are needed to promote the provision of adequate care at an early stage. The Brief Infant-Toddler Social and Emotional Assessment (BITSEA) was developed for this purpose. This study evaluates the effectiveness of the BITSEA to enhance social-emotional and behavioral health of preschool children. Methods and Design A cluster randomized controlled trial is set up in youth health care centers in the larger Rotterdam area in the Netherlands, to evaluate the BITSEA. The 31 youth health care centers are randomly allocated to either the control group or the intervention group. The intervention group uses the scores on the BITSEA and cut-off points to evaluate a child's social-emotional and behavioral health and to decide whether or not the child should be referred. The control group provides care as usual, which involves administering a questionnaire that structures the conversation between child health professionals and parents. At a one year follow-up measurement the social-emotional and behavioral health of all children included in the study population will be evaluated. Discussion It is hypothesized that better results will be found, in terms of social-emotional and behavioral health in the intervention group, compared to the control group, due to more adequate early detection, referral and more appropriate and timely care. Trial registration Current Controlled Trials NTR2035